CESAREANA EM SAGUIS: SAGUI-DE-TUFOS-BRANCOS (Callithrix jacchus) - Prestes, Nereu Carlos; Ferreira, João Carlos Pinheiro; Ferraz, Myrna Campos; Garofalo, Natache Arouca; Simões, Carla Regina Barbieri; Sabino, Fabiane Aparecida; Leal, Luciana Silva; Oba, Eunice (Veterinária e Zootecnia, 2023)
Callithrix jacchus is a small primate characteristic to the Brazilian Northeast. We considered relevant to report details on the anesthetic protocol and the surgical technique of cesarean sections applied in three cases of dystocia in C. jacchus. Animals were subjected to cesarean intervention because their small body size did not allow for less invasive obstetric maneuvers. The anesthetic protocol was shown to be efficient, safe and original in its equipment adaptations, by means of orotracheal intubation with a 14G catheter. The surgical procedure was relatively simple and did not offer a major challenge in the exposure of the uterus. The suture of the uterus, abdominal wall and skin did not present technical difficulties, however even the thinnest sutures used in dogs and cats may be considered too thick considering the marmosets’ small body size.